2007
DOI: 10.1111/j.1945-5100.2007.tb00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of 4 Vesta based on HED meteorites: Prospective study for interpretation of gamma ray and neutron spectra for the Dawn mission

Abstract: Abstract-Asteroid 4 Vesta, believed to be the parent body of the howardite, eucrite, and diogenite (HED) meteorites, will be investigated by the Dawn orbiting spacecraft. Dawn carries a gamma ray and neutron detector (GRaND) that will measure and map some major-and trace-element abundances. Drawing on HED geochemistry, we propose a mixing model that uses element ratios appropriate for the interpretation of GRaND data.Because the spatial resolution of GRaND is relatively coarse, the analyzed chemical compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 27 publications
4
53
0
Order By: Relevance
“…In order to estimate the proportions of the main eucritic and diogenitic lithologies involved during the genesis of the impact glasses found in howardites, we have performed mixing calculations using the Mona program (Metzner and Grimmeisen 1990). Usui and McSween (2007) have shown that combinations of three endmembers, namely, a diogenite (e.g., Shalka), a cumulate eucrite (e.g., Serra de Magé), and a low-Mg eucrite (e.g., Nuevo Laredo), reproduce all the major element abundances of HED meteorites satisfactorily (Usui and McSween 2007). Therefore, we have selected these endmembers for our calculations.…”
Section: Discussionmentioning
confidence: 99%
“…In order to estimate the proportions of the main eucritic and diogenitic lithologies involved during the genesis of the impact glasses found in howardites, we have performed mixing calculations using the Mona program (Metzner and Grimmeisen 1990). Usui and McSween (2007) have shown that combinations of three endmembers, namely, a diogenite (e.g., Shalka), a cumulate eucrite (e.g., Serra de Magé), and a low-Mg eucrite (e.g., Nuevo Laredo), reproduce all the major element abundances of HED meteorites satisfactorily (Usui and McSween 2007). Therefore, we have selected these endmembers for our calculations.…”
Section: Discussionmentioning
confidence: 99%
“…Cogent dynamical evidence suggests that Vesta, through its family of dynamically linked and basaltsurfaced vestoids, is the ultimate source of the HEDs (Binzel and Xu, 1993). Only one other basalt-surfaced belt asteroid has been observed (Hardersen et al, 2004), and the Vesta-HED hypothesis has won general acceptance (e.g., Righter and Drake, 1997;Gaffey, 1997;Keil, 2002;Usui and McSween, 2007). Wasson et al (1996) argued that the Vesta-HED link is not definite.…”
Section: Brecciation-mixing On the Hed Asteroidmentioning
confidence: 95%
“…Including cumulates, the range for Sm extends from 0.067 to 3.7 lg/g (Fig 3b; even excluding cumulates, eucrites range in La over a factor of five). Usui and McSween (2007) improve on the two-component mixing model by setting cumulate eucrite as a 3rd component. However, apart from having consistently near-negligible incompatible element contents in relation to noncumulate eucrites, cumulate eucrites in many ways show greater compositional range intragroup than in comparison with noncumulate eucrites; e.g., for Al 2 O 3 , MgO and Sc (Fig.…”
Section: Lithophile-element Complexitiesmentioning
confidence: 99%
“… Whole‐rock compositions of HED meteorites plotted on a) K versus Fe and b) Ti versus Fe diagrams. Data sources are given in Usui and McSween (2007) and in . Abbreviations are as in Fig.…”
Section: A New Mixing Modelmentioning
confidence: 99%